Risk factors for symptomatic venous thromboembolism during therapy for childhood acute lymphoblastic leukemia. Issue 178 (June 2019) - Mateos, M.K.; Trahair, T.N.; Mayoh, C.; Barbaro, P.M.; Sutton, R.; Revesz, T.; Barbaric, D.; Giles, J.E.; Alvaro, F.; Mechinaud, F.; Catchpoole, D.; Kotecha, R.S.; et al.
Abstract: Background: Symptomatic venous thromboembolism (VTE) is an unpredictable and life-threatening toxicity, which occurs early in childhood acute lymphoblastic leukemia (ALL) therapy. Approximately 5% of children will experience VTE which is treated with anticoagulation. Asparaginase and corticosteroids are etiologic factors for VTE, however other clinical factors may modify this risk. Procedure: We sought to i) assess published pre-treatment VTE risk factors ii) identify early clinical factors that were associated with VTE and iii) determine whether single nucleotide polymorphisms (SNPs) associated with VTE in non-cancer patients contributed to VTE in children with ALL. We performed a detailed, retrospective analysis of 1021 ALL patients treated between 1998 and 2013. Individual patient records were reviewed to ascertain VTE incidence and document treatment-related clinical variables. Results: The incidence of VTE was 5.1%. Extremes of weight at diagnosis (<5th or >95th centile) was an independent risk factor in multivariable analysis, when added to published risk factors of age ≥10 years and mediastinal mass. When factors during induction/consolidation were considered separately: bacteremia, elevated serum gamma-glutamyl transferase and bilirubin were associated with VTE occurrence. None of the SNPs associated with VTE in non-cancer populations were significantly associated with VTE in our cohort. Conclusion: We found two known risk factors (age ≥ 10 years and mediastinal mass) in a large cohort of children treated for ALL and identified other factors associated with VTE such as weight extremes at diagnosis, bacteremia, and abnormal liver function which warrant further study. These VTE risk factors may form the basis of future thromboprophylaxis trials. Highlights: Baseline and treatment-related factors were collected on 1021 consecutive children. Risk from age ≥10 years and mediastinal mass were validated in a BFM-based cohort. Baseline weight (<5th or >95th centile) was a risk factor for VTE in ALL therapy. Bacteremia, raised GGT and bilirubin during early therapy contributed to VTE risk. Genetic risk factors for VTE in ALL therapy may differ from non-malignant cohorts.